Therapeutic effects of hydro-alcoholic extract of Cynodon dactylon in hypercholesteremic rabbits - Seyyed Meysam Abtahi Froushani; Vahi Mohammadi; Ali Asghar Tehrani; Hadi Esmaeili Gouvarchin Ghaleh; Bahman Mansori Motlagh (Fasa University of Medical Sciences, 2018)
Background & Objective: This study was carried out to investigate the anti-atherosclerotic properties of hydro-alcoholic extract of C. dactylon in hypercholesterolemic rabbits. Materials & Methods: The standard regime was consisted of 5 normal rabbits that they were fed for 75 constitutive days with a standard regimen. Hypercholesterolemic group was consisted of 20 rabbits that were fed for 75 constitutive days with a high cholesterol (1% of food weight). These rabbits were allocated in 4 equal groups at the day after initiating the research, including animals with the hyper-cholesterol regime and treatment groups that daily received 100,200 or 400 mg/kg of the hydro-alcoholic extract of C. dactylon, respectively. Results: On the 45th and 75th day after beginning, other than blood sugar, the levels of triglyceride, total cholesterol, HDL and LDL, atherogenic index (LDL/HDL ratio), CRP, fibrinogen, serum levels of nitric oxide and malondialdehyde were significantly increased in rabbits with hypercholesteremic regime and without treatment compared to normal rabbits. The oral administration of the extract of C. dactylon at all doses for 30 constitutive days after the establishment of hypercholesterolemia, could significantly reduce the levels of cholesterol, triglyceride, LDL, and malondialdehyde. Moreover, 200 and 400 mg/kg of extract could significantly decrease the levels of the atherogenic index, CRP, fibrinogen, and malondialdehyde, and simultaneously increase the levels of HDL compared to rabbits with hypercholesterolemia. Only 400 mg/kg of extract could significantly decrease the serum levels of nitric oxide. Conclusion: Hydro-alcoholic extract of C. dactylon showed beneficial effects in reducing of hypercholesterolemia in the animal model.